Flood Risk Assessment for Zengcheng District of Guangzhou City Based on Complex Network Models - LI Bowen; ZHANG Yin; YANG Fang; ZHAO Hongjun (Renmin Zhujiang)
Under the dual influences of climate changes and urbanization,the frequent urban flood disasters exacerbate losses caused by the flood disaster chain and pose a serious threat to the public life safety and sound development of cities.Based on the disaster data from 1980 to 2020 in the Zengcheng District of Guangzhou,this paper builds a complex network model of disaster evolution by employing heavy rain as the disaster source and conducts disaster risk analysis.The vulnerability of the disaster network is evaluated by the calculation of the network average disaster path,edge betweenness,and connectivity.Meanwhile,the correlation between disaster events is analyzed by the co-occurrence rate of the events.The results show that high-intensity and short-duration heavy rain is the source of flood disasters in Zengcheng District,Guangzhou.Damage to water conservancy facilities is a key node affecting the vulnerability of the disaster network,and inundated farmland is the main cause of significant economic losses,with house flooding caused by water on the road surface being the biggest disaster risk.The results can provide references for risk control of the flood disaster chain in Zengcheng District,Guangzhou,and related emergency management decisions.